The Role of Mandatory Tender Offers in Protecting Minority Shareholders in Public Companies - Feivel, Maximilian; Abubakar, Lastuti (Dinasti Research, 2025)
The presence of minority shareholders in the ownership structure of listed companies often places them in a vulnerable position, especially in the event of a corporate takeover. To address this risk, Indonesian capital market law introduces the mandatory tender offer provision as stipulated in POJK No. 9/POJK.04/2018, which requires the new controlling party to purchase shares owned by other shareholders at a fair price. This research aims to legally evaluate the effectiveness of the mandatory tender offer as an instrument of legal protection for minority shareholders. The approach used is normative juridical with library research, examining primary legal materials such as relevant laws and regulations, as well as secondary legal materials in the form of books, scientific journals, and relevant articles. Based on the results of this study, it was found that the mandatory tender offer serves a protective purpose; however, the existing provisions still face challenges in terms of implementation, price transparency, and access to information for minority shareholders. Recommendations include strengthening supervisory mechanisms, updating regulations, and integrating the principles of fairness and accountability into public company governance